Analysis of the Cultivation of Pangerten and Gotong Royong Character Values Through Social Learning for Blind Students at SLB A YKAB Surakarta - Hasri Isnanto, Irham; Atik Catur Budiati; Yosafat Hermawan Trinugraha (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The unfocused cultivation of character values in the learning process is a problem in the field of education that can result in a lack of affective and pyschomotor aspects for students. Moreover, the lack of opportunities for the cultivation of character values is currently also affected to students with special needs, one of which is blind in SLB A YKAB Surakarta. Character problems are shown in the limited social skills of blind students who seem to still be independent (individualist) when interacting with others in SLB. Therefore, a good solution step is needed to help blind students fix the problem and grow their social skills through the process of instilling the character values of gotong royong and pangerten. This study aims to examine the extent to which blind students apply the cultivation of the character values of gotong royong and pangerten utilizing the stages of Bandura's social learning theory in the learning activities of SLB A YKAB Surakarta. The method used is qualitative with phenomenological approach. The research data sources were obtained from 6 informants, namely 2 teachers, 2 blind students, and 2 parents of students as research subjects. The results showed that blind students have implemented the process of instilling character values according to the stages of social learning. This is evidenced by the results of the actualization of students who have been able to bring up the attitude of togetherness as a reflection of the orientation of gotong royong and pangerten.